Structuring the Problem Space for Model‐Based Systems Engineering. Issue 1 (29th May 2019) - Wrigley, J. Craig
ABSTRACT: Systems engineering is evolving from a largely text‐based endeavour towards a more graphical and model‐based approach. While modelling of the structural aspects of a system is well developed, the modelling of requirements is still evolving. This paper proposes a traceable method for transforming textual functional requirements or business activities into required behaviours and proposes a multiscale approach to refining the behavioural descriptions into "atomic" behavioural requirements which can be satisfied either by existing systems or which can form the basis for development of new subsystems.